Hypochlorite-Activated Fluorescence Emission and Antibacterial Activities of Imidazole Derivatives for Biological Applications - Pham, Thanh Chung; Nguyen, Van Nghia; Choi, Yeonghwan; Kim, Dongwon; Jung, Ok Sang; Lee, Dong Joon; Kim, Hak Jun; Lee, Myung Won; Yoon, Juyoung; Kim, Hwan Myung; Lee, Songyi (Frontiers in Chemistry, 2021)
The ability to detect hypochlorite (HOCl/ClO−) in vivo is of great importance to identify and visualize infection. Here, we report the use of imidazoline-2-thione (R1SR2) probes, which act to both sense ClO− and kill bacteria. The N2C=S moieties can recognize ClO− among various typical reactive oxygen species (ROS) and turn into imidazolium moieties (R1IR2) via desulfurization. This was observed through UV–vis absorption and fluorescence emission spectroscopy, with a high fluorescence emission quantum yield (ՓF = 43–99%) and large Stokes shift (∆v∼115 nm). Furthermore, the DIM probe, which was prepared by treating the DSM probe with ClO−, also displayed antibacterial efficacy toward not only Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) but also methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum ß-lactamase–producing Escherichia coli (ESBL-EC), that is, antibiotic-resistant bacteria. These results suggest that the DSM probe has great potential to carry out the dual roles of a fluorogenic probe and killer of bacteria.
Keywords: antibacterial effect; fluorescent sensor; fluorogenic probe; hypochlorite sensor; probe–killer